KEY FACTORS AFFECTING AUDIT PRICING IN CAMEROON: EXPLORING ATTRIBUTES OF AUDIT FIRMS, CLIENTS, AND AUDITORS - Abioye, Michael (Ayden International Journal of Banking, Finance and Technology, 2024)
This study aims to investigate the determinants of audit fees in Cameroon, a country with a developing economy and an emerging market. The research utilized a quantitative research approach and collected data through a structured questionnaire from 171 audit firms operating in three regions of Cameroon, namely Littoral, Center, and North-West. The study employed multilinear regression to analyze the data and identify the significant determinants of audit fees in Cameroon. The study findings revealed that audit fees in Cameroon are influenced by various factors, including the experience of the audit firm, audit report lag, client complexity, duration of the mandate, and industry type. Specifically, the study found that audit firms with more experience tend to charge higher fees, while audit report lag, client complexity, and duration of mandate have a positive impact on audit fees. Moreover, the study found that the industry type also plays a significant role in determining audit fees, with firms in high-risk industries such as financial services charging higher fees. The research contributes to the literature on audit fees by providing insights into the factors that determine audit fees in Cameroon. The study's findings have practical implications for audit firms and clients in Cameroon, as they can use the results to negotiate fees and better understand the factors that influence audit fees. Overall, the study highlights the importance of considering various factors in determining audit fees, including the characteristics of the audit firm, auditee, and auditor.